2012
DOI: 10.1038/jp.2012.118
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the fetal progesterone receptor and a calcium-activated potassium channel isoform are associated with preterm birth in an Argentinian population

Abstract: Objective To investigate genetic etiologies of preterm birth (PTB) in Argentina through evaluation of single-nucleotide polymorphisms (SNP) in candidate genes and population genetic admixture. Study Design Genotyping was performed in 389 families. Maternal, paternal, and fetal effects were studied separately. Mitochondrial DNA (mtDNA) was sequenced in 50 males and 50 females. Y-chromosome anthropological markers were evaluated in 50 males. Results Fetal association with PTB was found in the progesterone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…This could be the basis for an effect of rs10895068 (+331G/A), found in the promoter region of the PGR gene, and is associated with increased PR‐B production, in part by introducing an additional TATA box, thus altering the PR‐A/PR‐B ratio . It also applies to rs194836, found in the PGR regulatory domain, and suggested to be involved in altered expression of PGR isoforms . Collectively, our findings underscore the contribution of altered PR isoform expression to RPL pathogenesis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This could be the basis for an effect of rs10895068 (+331G/A), found in the promoter region of the PGR gene, and is associated with increased PR‐B production, in part by introducing an additional TATA box, thus altering the PR‐A/PR‐B ratio . It also applies to rs194836, found in the PGR regulatory domain, and suggested to be involved in altered expression of PGR isoforms . Collectively, our findings underscore the contribution of altered PR isoform expression to RPL pathogenesis.…”
Section: Discussionsupporting
confidence: 56%
“…14 The hPR-A and hPR-B subtypes differ structurally in their N-terminal domain, which is shorter by 164 amino acids in PR-A compared with PR-B, and functionally, as PR-A is necessary for optimal uterine physiology and reproduction, whereas PR-B, which is active throughout gestation, assists in the maintenance of uterine quiescence. 15 The PR gene (PGR) is highly polymorphic, 16 and several polymorphic variants in the PGR gene have been associated with reproductive problems, 13,[16][17][18] including RPL. [6][7][8] A few studies have investigated the association of genetic variants in PGR with RPL, often with inconclusive findings.…”
Section: Introductionmentioning
confidence: 99%
“…Disagreements in the distribution between clinical subtypes may be due to a different ethnic mixtures across populations and regions[14,24]. Previous studies reported that genetic admixture in Argentina showed South Amerindian ancestry admixed with European [14, 15]. Furthermore, this sample excluded preterm twin pregnancies and preterm infants with malformations, which could modify the distribution of subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The premature delivery rate in the general population was 10.6% during the period of the study. The ethnic/race population was mostly South American Amerindian with Latin European admixture (98.7%)[14,15]. …”
Section: Methodsmentioning
confidence: 99%
“…36, 37 Additionally, the correlation between fetal and maternal genotypes makes interpretation of association findings difficult to ascribe to either source unless both the mother and the infant are genotyped. 38 Recently, studies have addressed a number of these shortcomings to provide some evidence of fetal genetic contributions to spontaneous 39, 40 and indicated 41, 42 preterm birth. Yet it remains to be seen whether replicable associations can be identified.…”
Section: Evidence For Fetal and Maternal Genetic Contributions To Thementioning
confidence: 99%